Effects of enzastaurin and its metabolites on the QT interval in cancer patients. (17th August 2015) - Welch, Pamela A.; Ng, Wee Teck; Darstein, Christelle L.; Musib, Luna; Lesimple, Thierry
Abstract: Preclinical and interim results from a clinical pharmacology study in patients with cancer indicated that enzastaurin might have the potential to prolong the QT. Rather than undertake a formal thorough QT study, the effect of enzastaurin on the QT was assessed by combining the QT corrected for heart rate (QTc) intervals from 3 clinical pharmacology studies totaling 85 patients with cancer receiving multiple therapeutic or supratherapeutic doses of enzastaurin. Neither a placebo nor an active control was used. Serial, replicate, time‐matched electrocardiograms were collected during a no‐drug baseline day and when enzastaurin and its major active metabolite, LSN326020, had achieved steady state. Plasma concentrations of enzastaurin and LSN326020 were determined at each electrocardiogram point to enable concentration–QT analyses. The cross‐study analysis showed that enzastaurin resulted in a statistically significant prolongation of the QTc at therapeutic and supratherapeutic doses. At an enzastaurin maximum plasma concentration (Cmax ) of 3660 nmol/L, the predicted QTc using Fridericia's formula (QTcF) interval and its 90% confidence interval was 17.72 milliseconds (16.52–18.92 milliseconds). Likewise, at an LSN326020 Cmax value of 1718 nmol/L, the predicted QTcF interval was 20.23 milliseconds (18.72–21.74 milliseconds). The concentration–QTcF slopes for enzastaurin and LSN326020 were positive and statistically significantly different from zero (all P < .05).